α-lipoic acid decreases oxidative stress even in diabetic patients with poor glycemic control and albuminuria - Borcea, Valentin; Nourooz-Zadeh, Jaffar; Wolff, Simon P; Klevesath, Martina; Hofmann Bowman, Marion; Urich, Heinz; Wahl, Peter; Ziegler, Reinhard; Tritschler, Hans; Halliwell, Barry; Nawroth, Peter Paul (Free radical biology and medicine, 1999)
In the present cross-sectional study, the influence of α-lipoic acid on markers of oxidative stress, assessed by measurement of plasma lipid hydroperoxides (ROOHs), and on the balance between oxidative stress and antioxidant defence, determined by the ratio ROOH/(α-tocopherol/cholesterol), was examined in 107 patients with diabetes mellitus. Patients receiving α-lipoic acid (600 mg/day for > 3 months) had significant lower ROOHs and a lower ROOH/(α-tocopherol/cholesterol) ratio than those without α-lipoic acid treatment [ROOH: 4.76 ± 2.49 vs. 7.16 ± 3.22 μmol/l; p < .0001] and [ROOH/(α-tocopherol/cholesterol): 1.37 ± 0.72 vs. 2.16 ± 1.17; p < 0.0001]. In addition, the influence of glycemic control and albuminuria on ROOHs and on the ratio of ROOH/(α-tocopherol/cholesterol) was examined in the presence and absence of α-lipoic acid treatment. Patients were subdivided into three groups based on (1) their HbA1 levels (<7.5, 7.5-9.5, and >9.5%) and (2) their urinary albumin concentrations (<20, 20-200, and >200 mg/l). Neither poor glycemic control, nor the presence of micro- or macroalbuminuria prevented the antioxidant effect of α-lipoic acid. Using stepwise multiple regression analysis, α-lipoic acid was found to be the only factor significantly predicting low ROOHs and a low ratio of ROOH/(α-tocopherol/ cholesterol). These data provide evidence that treatment with α-lipoic acid improves significantly the imbalance between increased oxidative stress and depleted antioxidant defence even in patients with poor glycemic control and albuminuria.
Im PDF wird in den Erscheinungsdaten fälschlicherweise Vol. 22 angegeben
Gesehen am 29.06.2021